Testbeds and Research Infrastructure. Development of Networks and Communities 7th International ICST Conference,TridentCom 2011, Shanghai, China, April 17-19, 2011, Revised Selected Papers - Korakis, Thanasis; Li, Hongbin; Tran-Gia, Phuoc; Park, Hong-Shik.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the proceedings of the 7th International ICST Conference, TridentCom 2011, held in Shanghai, China, in April 2011. Out of numerous submissions the Program Committee finally selected 26 full papers and 2 invited papers. They focus on topics as future Internet testbeds, future wireless testbeds, federated and large scale testbeds, network and resource virtualization, overlay network testbeds, management provisioning and tools for networking research, and experimentally driven research and user experience evaluation.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Software engineering; Computer simulation; Computer Science; Software Engineering; Simulation and Modeling; Programming Techniques; Computer Communication Networks; System Performance and Evaluation; Software Engineering/Programming and Operating Systems